2019
DOI: 10.1186/s40634-019-0187-3
|View full text |Cite
|
Sign up to set email alerts
|

The role of the medial plate for Pauwels type III femoral neck fracture: a comparative mechanical study using two fixations with cannulated screws

Abstract: Background: The biomechanical behavior of Pauwels type III fractures should be taken into consideration when performing internal fixation, since this repair should resist the shear force inherent in the vertical fracture line to the greatest extent possible. Recently, the use of a small fragment plate on the medial face of the femoral neck has been proposed by some authors, with satisfactory initial results. In the current study we analyze the mechanical role a medial plate used as a buttress plate for Pauwels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 33 publications
0
35
0
Order By: Relevance
“…In order to overcome the greater shearing force of Pauwels type III FNFs, some authors have proposed a treatment plan that uses screws and medial femoral neck plates. Related mechanical studies have shown [ 15 , 29 ] that the medial femoral neck plate can effectively resist shear forces. However, it is difficult to install a steel plate on the inner of the femoral neck because the femoral neck is deep and the area is close to the joint capsule of the hip joint.…”
Section: Discussionmentioning
confidence: 99%
“…In order to overcome the greater shearing force of Pauwels type III FNFs, some authors have proposed a treatment plan that uses screws and medial femoral neck plates. Related mechanical studies have shown [ 15 , 29 ] that the medial femoral neck plate can effectively resist shear forces. However, it is difficult to install a steel plate on the inner of the femoral neck because the femoral neck is deep and the area is close to the joint capsule of the hip joint.…”
Section: Discussionmentioning
confidence: 99%
“…In order to overcome the greater shearing force of Pauwels type III FNFs, some authors have proposed a treatment plan that uses screws and medial femoral neck plates. Related mechanical studies have shown [23,24] that the medial femoral neck plate can effectively resist shear forces. However, it is di cult to install a steel plate on the inner of the femoral neck because the femoral neck is deep and the area is close to the joint capsule of the hip joint.…”
Section: Discussionmentioning
confidence: 99%
“…Kunapuli et al 16 found that the medial femoral neck buttress plate enhanced the stability of cannulated screw and sliding hip screw constructs, signi cantly increased stiffness and load to failure. Giorfano et al 17 conducted a mechanical study to analyze the role of the medial buttress plate in Pauwels type III femoral neck fractures by comparing the resistance of two xation methods using three cannulated screws, and the results showed that the medial buttress plate combined with multiple cannulated screw xation provided a mechanically superior structure for Pauwels type III fractures. Additionally, Nwankwo et al 15 conducted a mechanical test with ten matched pairs of young cadaveric femurs and concluded that the application of medial plates to Pauwels Type III femoral neck fractures signi cantly decreased angular displacement and shear.…”
Section: Discussionmentioning
confidence: 99%